Stunting Prevention Strategy with a Local Wisdom Approach - Ipaenin, Rasmiyati; Salakory, Melianus; Riry, Roberth Berthy (GEOFORUM, 2024)
This study examines the use of sawi langit (Cyanthillium cinereum) as an alternative traditional treatment for worm infections, which is one of the causes of stunting in children. Stunting is a major health issue in Indonesia, with a high prevalence in Maluku Province. The study was conducted in Kelurahan Pandan Kasturi, Kecamatan Sirimau, Kota Ambon, using a descriptive qualitative approach to explore the use of sawi langit as a worm treatment passed down through generations. The findings show that the local community effectively uses sawi langit decoction to prevent and treat worm infections in children. This plant contains active compounds such as flavonoids and tannins, which have anti-parasitic and antioxidant properties, effectively minimizing the negative impact of worm infections while supporting overall health. The simple method of boiling sawi langit reflects the utilization of local wisdom as an affordable health solution. The study suggests the need for further research to detail the active compounds and conduct clinical trials on humans to optimize its medical benefits. Thus, sawi langit has the potential to contribute to stunting prevention through a natural, affordable approach, while also preserving valuable traditional knowledge.